(untitled) (Eurasian Journal of Philology Science and Education, 2015)
The article reveals the originality of the concept "honor" in the Russian and Kazakh proverbs. Found a close logical connection of the concept "honor" of the concepts: the conscience, responsibility, honor, duty, self-respect, dignity, honesty, decency, integrity, unblemished reputation, self-esteem. Logical-associative links concept "honor" in the Russian language are identical to the concept of the Kazakh Relations Ar-namys. Found that in the Kazakh and Russian honor is an indication of kindness, morality, one of the core values. Honor - moral health, the manifestation of the mind, wisdom, infamy - the disease. The peculiarity of the Kazakh proverbs manifested in turning to jigit. Jig - conscience and pride of the people, an example to follow. The concepts of "brave" and "honor" in the Kazakh paremiology inextricably linked. In Russian proverbs treatment facilities are not specified. In the article, so the examples of ethnic and cultural stereotypes presented in the Kazakh and Russian proverbs, confirming the idea that language reflects Paremiological fund human and national.